2023
DOI: 10.1177/11206721231155519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phakic collamer intraocular lens with a central hole on structural tests measurements of retinal nerve fiber layer and macula

Abstract: Aim To evaluate whether the Visian Implantable Collamer Lens with a central port (V4c ICL®; STAAR Surgical, Switzerland) affects the retinal nerve fibre layer (RNFL), macula and optic nerve head (ONH) measurements obtained by optical coherence tomography (OCT), and Heidelberg Retina Tomography (HRT). Methods This prospective study included myopic patients undergoing V4c ICL® implantation. RNFL thickness, macular thickness, ganglion cell analysis (GCA) and ONH main parameters were evaluated with RTVue OCT (Opto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Interestingly, these changes were not found to be associated with SER, AL, or age. Our findings align with those of Pachon et al, who reported increased macular thickness at postoperative months 1 and 12 following ICL V4c implantation [7]. Conversely, Xu et al found no significant changes in central retinal thickness (CRT) at postoperative weeks 1, 3, and 6, as well as blood flow density of superficial and deep macular fovea [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, these changes were not found to be associated with SER, AL, or age. Our findings align with those of Pachon et al, who reported increased macular thickness at postoperative months 1 and 12 following ICL V4c implantation [7]. Conversely, Xu et al found no significant changes in central retinal thickness (CRT) at postoperative weeks 1, 3, and 6, as well as blood flow density of superficial and deep macular fovea [24].…”
Section: Discussionsupporting
confidence: 91%
“…Compared to prior ICL models, the V4c model has exhibited a substantial reduction in reported complications due to enhanced aqueous humor flow and preserved anterior segment physiology [4][5][6]. However, limited research exists on the impact of the V4c model on retinal and choroidal morphology, which are vital for maintaining patients' visual function [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%